THE APPLICATION OF LEAN MANAGEMENT METHOD IN OPTIMIZING ADMINISTRATIVE EFFICIENCY IN SCHOOLS - Murnizu, Musran; Dannur, Moh; Zakaria, Nanang; Alfiansyah, Alfiansyah; Pono, Maat (Jurnal Konseling Pendidikan Islam, 2024)
This study aims to explore the implementation of the Lean Management Method in optimizing administrative efficiency in Indonesian schools. The research method used is a qualitative approach involving data collection through in-depth interviews with relevant stakeholders in several schools. The research findings indicate that the application of Lean Management principles, such as identifying waste in administrative processes, using Lean tools and techniques such as Value Stream Mapping and 5S, and fostering a culture of Kaizen, has had a positive impact on improving productivity and the quality of educational services in these schools. However, challenges such as resistance to change and a lack of understanding of Lean concepts are also identified as obstacles that need to be addressed in implementing Lean Management in the education sector. The conclusion of this research emphasizes the importance of considering social and cultural aspects in the change process, as well as involving all members of the school community in improvement efforts. Recommendations for further research include exploring the long-term impact of Lean Management implementation on educational quality and stakeholders, as well as delving into more effective strategies to address challenges in implementing Lean Management in the Indonesian education environment.